The Comparison Between the Expectations and Perceptions of Thai Tourists Towards Communication Channels of the Secondary Destination Image of Ratchaburi Province, Thailand - Saisud, Revita; Bunjongmanee, Parinya; Louang-on, Anchalee (KKBS Journal of Business Administration and Accountancy, 2023)
The purposes of this research towards the communication channels of the secondary destination image, Ratchaburi were (1) to study the Thai tourists’ expectations, (2) to study the Thai tourists’ perceptions, (3) to compare the expectations and perceptions of Thai tourists, (4) to study how the Thai tourists’ expectations influencing the re-visiting tourists, and (5) to study how the Thai tourists’ perceptions influencing the re-visiting tourists. This research was collected using questionnaires with accidental sampling method from 400 Thai tourists and analyzed by descriptive and inferential statistics. The research results found that (1) the demographic characteristics varied with different opinion levels approaching the perceptions toward the communication channels of the secondary destination image at the significance level of 0.05. (2) The demographic characteristics varied with different opinion levels approaching the expectations toward the communication channels of the secondary destination image at the significance level of 0.05. (3) The average of opinion levels approaching the perceptions was significantly higher than the expectations toward the communication channels of the secondary destination image at the significance level of 0.05. (4) The opinion levels approaching expectations toward the communication channels of the secondary destination image correlated with the re-visiting tourists at the significance level of 0.05. (5) The opinion levels approaching perceptions toward the communication channels of the secondary destination image correlated with the re-visiting tourists at the significance level of 0.05. The research results have augmented the academic implication as to the strategic guideline following tourists and communication channels of Ratchaburi, the tourist destination with a lack of destination image encouragement. Therefore, this research is an advantage for creating a circular economy and improving the quality of life.